2020
DOI: 10.11648/j.plant.20200802.12
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Response of Yield Components and Yield of Bread Wheat to NPK Fertilizers at Hidebu Abote District of North Shewa Zone, Oromia

Abstract: A field experiment was carried out on nitisols of Hidebu Abote district, North Shewa Zone, Oromia where wheat production is severely constrained by lack of an appropriate rate and types of fertilizer recommendation to evaluate wheat crop response to NPK fertilizer application. Fifteen NPK nutrients levels were considered and applied as treatments along with control (no fertilizer) at yaya Deka Bora peasant association were arranged in randomized complete block design (RCBD) with three replications at two farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although there was no industrialization in the study area, continuous agrochemical chemical application was identified in Hidabu Abote Woreda, which may contribute to the accumulation of metals in the soil (Abebe et al., 2020 ; Feyisa et al., 2022 ). The pH of the soil in Hidabu Abote Woreda has been shown to be somewhat acidic, which may affect the availability of nutrients and plant uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no industrialization in the study area, continuous agrochemical chemical application was identified in Hidabu Abote Woreda, which may contribute to the accumulation of metals in the soil (Abebe et al., 2020 ; Feyisa et al., 2022 ). The pH of the soil in Hidabu Abote Woreda has been shown to be somewhat acidic, which may affect the availability of nutrients and plant uptake.…”
Section: Resultsmentioning
confidence: 99%